Does every hotel room need a minifridge? Empirical evidence from consumer self-reports and an automatic sensor-based system measuring electricity consumption and guest use - Sara Dolnicar; Danyelle Greene; Siamak Layeghy; Marius Portmann (Annals of Tourism Research Empirical Insights, 2024)
Most hotel rooms contain a minifridge. Manufacturing, operating, and disposing of minifridges is environmentally unsustainable, and costs money. Given the potential to reduce carbon emissions by reducing the number of hotel minifridges, we ask whether it is necessary to provide minifridges in each room. We collect (1) electricity consumption and guest use data for 19 minifridges across four hotels using a newly developed automatic monitoring system, and (2) survey data to gain insights into hotel guests' stated preferences. Results indicate that electricity use is independent of minifridge use and that only a subset of hotel guests use the minifridge. Most guests prefer having a minifridge, but do not react negatively to it not being available. It may be worth reviewing the current default inclusion of minifridges and considering alternative minifridge provision systems.
Keywords: 330; Benchmarking; Engineering; Environmental performance; Experiments; Sustainable tourism